CFD modelling of energy storage room fire with low-pressure water mist extinguishing - Brzeziński, Mateusz; Brzezińska, Dorota; Brzezińska, Maria (Instal, 2025)
The increasing use of lithium-ion batteries has made their fire prevention and protection a critical aspect for users. This article presents the application of computational fluid dynamics (CFD) modelling of energy storage room fire and its low-pressure water mist extinguishing. Real-scale experiments and CFD simulations indicated that without fire extinguishing, battery fires can lead to uncontrolled temperature rises, jet flames, or explosions. While the installation of water mist systems can prevent the fire propagation, lower the temperature, and control fire propagation on adjacent modules, even in complex battery systems. The CFD simulations proved the effectiveness of this approach in the design of water mist systems in energy storage rooms. The article presents a structured research procedure in which the computer model allows for the analysis of fire development from a single cell to a full-scale energy storage facility.
Keywords: battery fire; energy storage room; CFD